A Novel Antioxidant, Hydrogen-Rich Coral Calcium Alters Gut Microbiome and Bile Acid Synthesis to Improve Methionine-and-Choline-Deficient Diet-Induced Non-Alcoholic Fatty Liver Disease - Hung-Tsung Wu; Chin-Shiang Tsai; Ting-Hsing Chao; Horng-Yih Ou; Liang-Miin Tsai (MDPI AG, 2024)
The prevalence of non-alcoholic fatty liver disease (NAFLD) has dramatically increased in recent years, and it is highly associated with metabolic diseases, as well as the development of hepatocellular carcinoma. However, effective therapeutic strategies for the treatment of NAFLD are still scarce. Although hydrogen-rich water shows beneficial effects for hepatic steatosis, the inconvenience limits the application of this antioxidant. In light of this, hydrogen-rich coral calcium (HRCC) was developed due to its convenience and quantifiable characteristics. However, the effects of HRCC on NAFLD are still unknown. In the present study, we found that HRCC treatment improved methionine-and-choline-deficient diet (MCD)-induced hepatic steatosis, increased aspartate aminotransferase and alanine aminotransferase levels, and elevated hepatic inflammatory factor expressions in mice. In addition to the increased expressions of antioxidative enzymes, we found that HRCC increased the expressions of bile acid biosynthesis-related genes, including Cyp8b1 and Cyp27a1. Increased hepatic bile acid contents, such as muricholic acids, 23 nor-deoxycholic acid, glycoursodeoxycholic acid, and cholic acids, were also confirmed in MCD mice treated with HRCC. Since the biogenesis of bile acids is associated with the constitution of gut microbiome, the alterations in gut microbiome by HRCC were evaluated. We found that HRCC significantly changed the constitution of gut microbiome in MCD mice and increased the contents of Anaerobacterium, Acutalibacter, Anaerosacchariphilus, and Corynebacterium. Taken together, HRCC improved MCD-induced NAFLD through anti-inflammatory mechanisms and by increasing antioxidative activities. Additionally, HRCC might alter gut microbiome to change hepatic bile acid contents, exerting beneficial effects for the treatment of NAFLD.